Assessment of Agricultural information needs in African, Caribbean & Pacific (ACP) States for CTA’S Products and Services: Phase 1: Caribbean: Country Study: Antigua and Barbuda - Williams, Roberta; Evan-Wong, Sue (Technical Centre for Agricultural and Rural Cooperation, 2005)
This study commissioned by CTA aims to identify agricultural information needs of key actors / beneficiaries for CTA products and services, potential actors ..and, to develop some baseline data to facilitate subsequent monitoring activities.